PENGEMBANGAN ELEKTRONIK LEMBAR KERJA PESERTA DIDIK (E-LKPD) BERBASIS LIVEWORKSHEET PADA MATERI MENGENAL KARAKTERISTIK WILAYAH UNTUK SISWA KELAS V SEKOLAH DASAR - Syifa Nur Hasanah; Zaka Hadikusuma Ramadan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to identify the development and validity of liveworksheet-basedElectronic Student Worksheets (E-LKPD) as learning resource innovations thatcan be used in the learning process. This research uses a development researchapproach with the ADDIE model which consists of three stages, namely analysis,design, and development. Data was collected through interviews andquestionnaires addressed to validator experts and response questionnaires. Thevalidation results by the subject matter expert obtained a final score of 95.31%"Very valid", linguists obtained 92.5% "Very valid", and design experts 92.85%"Very valid". Overall, the validity of liveworksheet-based E-LKPD obtained anaverage score of 93.55% so that E-LKPD based on liveworksheet is categorizedas "Very valid" without revision and is already feasible to use. This liveworksheet-based E-LKPD also received responses from teachers and students with a scoreof 100% with a very good category, so that the liveworksheet-based E-LKPD wasdeclared suitable for use in the learning process.